SWOT Analysis of Online Teaching During Lock Down: Blended Teaching the Way Forward - Gupta, Ritu Mittal; Sharma, Preeti (Indian Journal of Extension Education, 2020)
COVID-19 pandemic had made even the educational institutions shut down for an uncertain time. At this time, online teaching was initiated by educational institutions. The current study was an attempt to analyze the strengths, weaknesses, opportunities and threats related with online teaching during lock down. A survey was conducted using google form from students of Punjab Agricultural University, Ludhiana. Three hundred and seventy students responded to the developed survey. Data regarding mode of teaching was again collected from the respondents after a gap of six months. The findings revealed that initially, classes were taken through zoom app but later, most of the teachers shifted to google meet. Students agreed that online teaching has the strengths of accessing at anytime, anywhere, saves time, promotes retention of learning, and reduces cost of commuting / transportation. Among weaknesses, its highly dependency on network connection, teacher’s inability to check on each and every student, failure to substitute classroom teaching, lack of transparency in conducting online examination and limited assessment and feedback were reported. A large number of the respondents complied that online learning gave them the opportunity to connect with teachers and other students from far-away places at one platform, it is best available option during lock down like situations. However, respondents perceived threat of cybercrime while pursuing online learning. It is suggested that in future, blended learning can be opted by incorporating online teaching along with classroom teaching to overcome weaknesses and threats of online teaching while making best use of its strengths and opportunities.
Keywords: COVID-19; Lockdown; Online teaching; Opportunities; Strength; SWOT; Threats; Weakness